Effectiveness of Using Koin Muatan Teaching Aids to Improve Numeracy Skills - Deda, Yohanis Ndapa; Laja, Yosepha Patricia Wua; Talan, Nelciana (International Journal of Research in Education, 2024)
Literacy Numeracy is currently one of the topics in learning mathematics. A person is said to have Numerical Literacy Ability to count, distinguish and process various data symbols, and perform basic mathematical operations to fix the problem. However, the problem that is always faced by students today is the lack of understanding of the basic concepts of mathematics, one of which is integer arithmetic operations, so it won't be easy to understand more abstract mathematical concepts. The low numeracy literacy ability is due to the learning process not applying the suitable model or media. Therefore, it is necessary to have appropriate learning media so that students understand concepts well and can improve Numerical Literacy skills. One of the proper media or teaching aids for learning integer arithmetic operations is Koin Muatan, made with paper as a base material that symbolizes positive and negative charges. The type of research used was experimental research, a one-group pretest-posttest design pre-experimental design on 21 SD GMIT 4 Kefamenanu students. Data collection techniques were observation, tests and documentation. At the same time, the data analysis technique used is descriptive statistical analysis, inferential analysis and N-Gain analysis. The t-test results are used to test the average value before and after being given treatment and whether there is a significant effect. Based on the results of the tests performed, the average pretest and posttest values were 43.51 and 70.79. An N-Gain test was carried out to determine the large increase in numeracy literacy skills so that an N-Gain value of 0.45 was included in the moderate category. This result proves an increase in numeracy literacy skills after students are given the learning treatment using the Koin Muatan teaching aids at SD GMIT 4 Kefamenanu.